1993
DOI: 10.1007/bf02535772
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid increases permeability of lipid vesicles and tumor cells

Abstract: Docosahexaenoic acid (DHA), a long-chain polyunsaturated omega 3 fatty acid, is tested to determine its mode of action as an anti-cancer agent. We demonstrate that DHA can increase the permeability of phospholipid vesicles, as monitored by vesicle swelling in isosmolar erythritol and leakage of sequestered carboxyfluorescein, and T27A tumor cells, as monitored by swelling in isosmolar erythritol and release of sequestered 51Cr. DHA was incorporated into lipid vesicles as either the free fatty acid or as 1-stea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
1
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(49 citation statements)
references
References 32 publications
1
45
1
2
Order By: Relevance
“…Demel et al [78] demonstrated that DHA incorporated into the sn-2 position of PC enhanced permeability to glucose, erythritol and glycerol. Measuring bilayer permeability to erythritol and carboxyfluorescein, Stillwell et al [79] established that DHA enhanced bilayer permeability 2 to 3 fold more than oleic acid in identical phospholipids. Huster et al [80] used 17 O NMR to follow water permeability across lipid bilayers.…”
Section: Permeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Demel et al [78] demonstrated that DHA incorporated into the sn-2 position of PC enhanced permeability to glucose, erythritol and glycerol. Measuring bilayer permeability to erythritol and carboxyfluorescein, Stillwell et al [79] established that DHA enhanced bilayer permeability 2 to 3 fold more than oleic acid in identical phospholipids. Huster et al [80] used 17 O NMR to follow water permeability across lipid bilayers.…”
Section: Permeabilitymentioning
confidence: 99%
“…DHA as either the free fatty acid or as part of a mixed chain PC (18:0-22:6PC) enhanced SUV fusion to a much larger extent than did PCs with other, less unsaturated fatty acids [85]. When T27A tumor cells were fused with vesicles containing 18:0-22:6PC, the tumor plasma membrane became leakier [79], had altered expression of surface proteins [89], altered domain structure [90], decreased cell deformability [91], increased cytolysis by cytotoxic T-lymphocytes [86] and decreased cell longevity [3,89]. Upon fusion with SUVs made from 18:0-XPC, where X is stearic, oleic, α-linolenic, arachidonic, eicosapentaenoic or DHA, only DHA was cytotoxic [88].…”
Section: Bilayer Instability: Vesicle Fusion Exfoliation and Flip-flopmentioning
confidence: 99%
“…This important ®nding raised many questions, but in particular the issue about the biochemical and biophysical mechanisms that lead to their essentiality. To date, a multitude of mechanisms have been explored, for example, their eects on; the structural integrity and¯uidity of membranes [33,130]; enzyme activities [80,120,125]; lipid-protein interactions [117]; and their role as precursors for eicosanoids, such as prostaglandins, leukotrienes and thromboxanes.…”
Section: Introductionmentioning
confidence: 99%
“…11) An exogenous supplement of HUFAcontaining PL also affects the membrane environment and influences various cellular functions. [12][13][14] We previously reported that the enhancing effect of DHA-PL on RAinducing differentiation was stronger than that of DHA. 15) Since signal transduction enzymes such as protein kinase C (PKC) 16,17) and adenylate cyclase 18) are affected by specific molecular species of PLs, the membrane modification by HUFA-PL may be effective to enhance the sensitivity of leukemia cells to differentiation-inducing drugs.…”
mentioning
confidence: 99%